Hydroponic Provisions for Food Production During the Covid-19 Pandemic Necessitated Restricted Land Use - Sembiring, Pasukat; Suyanto; Marpaung, Jonathan Liviera (Talenta Publisher, 2023)
In a time of pandemic like this, people are being demanded to reduce activity outside the house, many activities are spent with at home alone such as, working from home, learning from home and not a few lose their jobs because some companies are closed. Some of these things often lead to a decrease in the productivity of the community and a rise in the cost-effectiveness of the society, so that's one of the activities that can boost the production of society. There's a lot of business opportunities to do during the Covid 19 pandemic. This dedication will train the PKK community of Muliorejo Village in the use of limited land with hydroponics type Deep Flow Technique (DFT). This activity aims to be able to help the community in the economy that exists in the society. To tackle the economic problems of a pandemic, a community can start a business by leveraging what's in its surroundings and transforming it into what the environment needs as well. The result is that the Muliorejo village PKK community understands the importance of productivity in the pandemic era and utilizes limited household land so that it can meet household food needs with the use of hydroponics type DFT.